Birthing the dragon - Ridzuan, Raihana; Adnan, Mohd Ridzuan; Qamaruz Zaman, Faridah (University Putra Malaysia, 2012)
Dragon fruit or buah naga is one of the popular tropical fruits in Malaysia. The discoverers might have given this name as the fruit has scale-like leaves and fiery colour associated with the dragon. This exotic fruit is utilized as fruit beverages, jam, jellies and ices because of its colour, aroma and taste. In Malaysia, dragon fruit crop cultivation shows a great expansion due to the high market demands since 2006. Hence, the advance biotechnology practices in the agricultural sector are very important to meet the current and future demands in dragon fruit production.